Direct democracy and local government efficiency - Zareh Asatryan; Kristof De Witte (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
This paper studies the role of direct democracy in ensuring efficient and cost effective provision of goods and services in the public sector. The sample consists of the population of municipalities in the German State of Bavaria, where in the mid-1990s considerable direct democratic reforms granted citizens with wide opportunities to directly participate in local affairs through binding initiatives. Using information on the municipal resources and the municipal provision of public goods, and applying a fully non-parametric approach to estimate local government overall efficiency, the analysis shows that more direct democratic activity is associated with higher government efficiency. This result suggests that more inclusive governance through direct decision-making mechanisms may induce more accountable and less inefficient governments.
urn:nbn:de:bsz:180-madoc-361213
Keywords: C14; D7; H7; 330; Direct democracy; Public sector efficiency; Conditional efficiency